Mobile forms of carbon in trees : metabolism and transport - Dominguez, Pia Guadalupe (2022)
Plants constitute 80% of the biomass on earth, and almost two-thirds of this biomass is found in wood. Wood formation is a carbon (C)-demanding process and relies on C transport from photosynthetic tissues. Thus, understanding the transport process is of major interest for understanding terrestrial biomass formation. Here, we review the molecules and mechanisms used to transport and allocate C in trees. Sucrose is the major form in which C is transported in plants, and it is found in the phloem sap of all tree species investigated so far. However, in several tree species, sucrose is accompanied by other molecules, notably polyols and the raffinose family of oligosaccharides. We describe the molecules that constitute each of these transport groups, and their distribution across different tree species. Furthermore, we detail the metabolic reactions for their synthesis, the mechanisms by which trees load and unload these compounds in and out of the vascular system, and how they are radially transported in the trunk and finally catabolized during wood formation. We also address a particular C recirculation process between phloem and xylem that occurs in trees during the annual cycle of growth and dormancy. A search of possible evolutionary drivers behind the diversity of C-carrying molecules in trees reveals no consistent differences in C transport mechanisms between angiosperm and gymnosperm trees. Furthermore, the distribution of C forms across species suggests that climate-related environmental factors will not explain the diversity of C transport forms. However, the consideration of C-transport mechanisms in relation to tree–rhizosphere coevolution deserves further attention. To conclude the review, we identify possible future lines of research in this field.